Potential of Blended Learning at High Schools in Hanoi - Nguyen, Hoang Trang; Hung, Mai Van; Quynh, Nguyen Thi Thuy (VNU Journal of Science: Education Research; Vol 36 No 2DO - 10.25073/2588-1159/vnuer.4417, 2020)
This study focuses on considering potential for the application of the blended learning model at high schools in Hanoi City. Surveyed in this study are 550 students and 30 teachers in 3 high schools in Hanoi. The nominal scale and convenience sampling method were used. The results of the study showed that there are advantages and disadvantages of applying the model, such as the good ability to furnish personal technology equipment; the habit of teaching and learning with the support of information technology; inequality in teachers’ knowledge and experience of blended learning; the fact that teachers’ teaching objective is substantially based on traditional teaching. For this reason, some solutions were proposed with a view to efficiently applying the blended learning model, including special importance to the increase of teachers’ and students’ awareness, investment in infrastructure development, application of the blended learning model according to a roadmap, and promulgation of a policy on fostering and encouraging teachers to apply the blended learning model. The results of this study will provide further research ideas about selecting the most appropriate approach to use when designing blended courses at high schools in Hanoi.